Materialistic, Hedonistic, and Consumptive Lifestyle Trends: An Analysis The Learning Materials Of Al-Qur’an Hadith At The Madrasah Tsanawiyah Level - Nurullita Fikri Zahwa; Zainur Huda; Adona, Putri (Al Bahri: Journal of Islamic Education, 2024)
Materialistic, hedonistic, and consumptive lifestyles in this case the excessive lifestyle and miserly attitude are on two different sides. Because these two traits are clearly contrary to the concept of simplicity that Islam wants. Therefore, this paper will discuss the prohibition of materialistic, hedonistic and consumptive lifestyles in the Qur'an and Hadith. The research method used is library research, which is a method of collecting data by understanding and studying theories from various literatures related to the research. After conducting in- depth research, the author can find that the nature of materialism (life values that emphasize or attach importance to the ownership of material goods or wealth), Hedonism (Pleasure of life), Consumptive (behaviour or lifestyle that likes to spend money without considering carefully). Islam firmly rejects the attitudes of these three lifestyles in the form of prohibiting extravagance on the one hand and miserliness on the other. Because these three traits are clearly contrary to the concept of simplicity that Islam wants. As Allah says in QS. Al-Hadid: 20, QS. At-Takatsur: 1, and QS. Al-Isra: 17. The study of the Al-Quran and Hadith, a Muslim should use his wealth for useful things and not be used for vain things.